Integrating Chronic Obstructive Pulmonary Disease Treatment With 8-Week Tai Chi Chuan Practice: An Exploration of Mind-Body Intervention and Neural Mechanism - Shen, Haoran; Chen, Li-Zhen; Hu, Zhuoer; Yao, Xiaoyan; Yang, Tao; Zhang, Lan; Tu, Qiang; Li, Guangxi; Wei, Gao-Xia (Frontiers in Human Neuroscience, 2022)
Objective: The aim of this study is to explore the effect of integrating routine treatment with Tai Chi Chuan (TCC) intervention on clinical symptom of the patients with Chronic Obstructive Pulmonary Disease (COPD) from clinical and neurological perspectives. Methods: Twenty COPD patients were recruited for regular treatment combining with 8-week TCC rehabilitative training. Clinical symptoms were evaluated by Chronic Obstructive Pulmonary Symptom Assessment Scale (CAT) and Modified Dyspnea Scale (mMRC) at baseline and after treatment. Resting-state MRI scan was also performed with multiline T2-weighted echo-planar imaging (EPI) to acquire their functional images before and after the treatment. TCC rehabilitation involved a total of 8 weeks practice with 90 mins per time and 3 times a week. Results: After 8-week integrating routine treatment with TCC training, the patient’s clinical symptoms were improved significantly. Imaging analysis showed that COPD patients exhibited decreased Degree Centrality (DC) in right inferior frontal gyrus (IFG), right middle frontal gyrus, bilateral cingulate cortex, bilateral precuneus, and right precentral gyrus. Moreover, correlation analysis found that the decreased DC in the right IFG was positively correlated with the CAT improvements. Conclusion: The routine treatment involving TCC rehabilitation training could improve the clinical symptoms of COPD patients. The right IFG might be a key brain region to contribute to the neural mechanism underlying integrative intervention on clinical symptom in COPD. These findings provide neurological evidence for treating COPD rehabilitation training with mind-body practice based on Chinese culture to some extent, which also advance the understanding of clinical efficacy of TCC as the adjuvant technology from neuroscience perspective.